2019
DOI: 10.18517/ijaseit.9.2.7909
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Sensory Properties of Pumpkin (Cucurbita moschata D) and Arrowroot (Marantha arundinaceae L) Starch-based Instant Porridge

Abstract: Pumpkin is a potential source of vitamin A and antioxidant. Arrowroot starch as the source of carbohydrates contains a low glycemic index. However, the utilization of pumpkin and arrowroot starch as the source of food products is still limited. Both ingredients can be processed into nutritious food with practical servings. The objective of the research was to investigate the effect of pumpkin and arrowroot starch ratio and the rotation speed of the drum dryer on the physiochemical properties and the acceptabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Treatment with chayote juice at a dose of 1 mL.100g -1 of body weight of rats per day decreased the triglycerides, total cholesterol, and LDL and increased HDL [22]. Pumpkin porridge and arrowroot starch at a 5:1 had a resistant starch content of 11.97% [23], affecting blood glucose levels in rats because resistant starch is not easily digested into glucose.…”
Section: Blood Glucose Levels Of Ratsmentioning
confidence: 99%
“…Treatment with chayote juice at a dose of 1 mL.100g -1 of body weight of rats per day decreased the triglycerides, total cholesterol, and LDL and increased HDL [22]. Pumpkin porridge and arrowroot starch at a 5:1 had a resistant starch content of 11.97% [23], affecting blood glucose levels in rats because resistant starch is not easily digested into glucose.…”
Section: Blood Glucose Levels Of Ratsmentioning
confidence: 99%
“…Based on pasting characteristics, starch varieties that are suitable to be ingredients of instant porridges are clustered among C-type starches. These starches exhibit limited granule swelling, no peak viscosity, short gelatinization times, and high water absorption indexes [7,8]. Mulyono et al [9] reported that adlay flour has a relatively high peak viscosity (2767-3958 cP), a long gelatinization time (356-438 s), and high breakdown viscosity values (1442-1585 cP).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the applications are currently limited to consumption, after peeling, and subsequently fried, boiled, or used to create crepes and various foods. Furthermore, advanced processing and starch use are not common, although there have been reported health benefits in the fruit form, as seen with pumpkin [18]. This is due to the presence of several compounds, including alkaloids and saponins, characterized by the capacity to reduce blood glucose in people with diabetes mellitus and uric acid levels [10].…”
Section: Introductionmentioning
confidence: 99%